The world news prism : challenges of digital communication - Hachten, William A., 1942-2018; Scotton, James F., ....- (Chichester : Wiley-Blackwell, 2012)
Fully revised and updated, the eighth edition of The World News Prism analyzes the changing role of transnational news media in the 21st-century globalized world and its impact on rapidly changing news events. Table of contents: Preface to the Eighth Edition Introduction 1 News Communication for a Global System 2 Changing Ideologies of Press Control 3 Global News Under Stress 4 Digital Media: Global, Interactive, and Free 5 The Whole World is Watching: Impact of Great News Events 6 Globalization of Media and Language 7 China: New Media In An Old Political World 8 The Middle East: Media Storms in the Desert 9 India and Africa: Contrasts in Development 10 Foreign News in Flux 11 War Reporting: Fire and Misfire 12 Public Diplomacy and Propaganda 13 Forecast: Changeable with Cloudy Periods Selected Bibliography Index
Keywords: Digitale communicatie; Digitale journalistiek